PENGARUH PROFITABILITAS, OPERATIONAL CASH FLOW, DENGAN CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI VARIABEL MODERASI TERHADAP PENGHINDARAN PAJAK (TAX AVOIDANCE) PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Delphia Novianti; Jaeni Jaeni (Jurnal Riset Akuntansi Politala, 2023)
This study aims to analyze the effect of Profitability, Operational Cash Flow and Corporate Social Responsibility (CSR) as a moderating variable on Tax Avoidance. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. In this study, a sample of companies that were obtained and met the criteria were 200 financial report data which, after going through the normality test, became 141 observations. The method used in sampling in this study is using purposive sampling method. The analysis used is multiple linear regression analysis which functions to involve moderating variables in building the relationship model. The moderating variable acts as a variable that can strengthen or weaken the relationship between the independent variables and the dependent variable, which is preceded by the classic assumption test which consists of a formality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. Meanwhile, hypothesis testing was carried out using the F test and t test. The results of data analysis from this study showed that Profitability had no effect on Tax Avoidance, whereas Operational Cash Flow had a positive effect on Tax Avoidance. Meanwhile, Corporate Social Responsibility (CSR) is not able to moderate the influence of Profitability and Operational Cash Flow on Tax Avoidance. Â